Evaluation of the Mercy TAPE: Performance Against the Standard for Pediatric Weight Estimation - Abdel-Rahman, Susan M. (2013)
OBJECTIVES: We assessed the performance of two new devices (2D- and 3D-Mercy TAPE) to implement the Mercy Method for pediatric weight estimation, and contrasted their accuracy with the Broselow method. METHODS: We enrolled children 2 months through 16 years of age in this prospective, multi-center, observational study. Height/length, weight, humeral length and mid-upper arm circumference were obtained for each child using calibrated scales and measures. We then made measurements using blinded versions of the 2D- and 3D-TAPEs. Using height/length data, we calculated the weight estimated by the Broselow method. We contrasted measures with mean error, mean percentage error, and percent predicted within 10 and 20% of actual. RESULTS: 624 participants (median: 8.4 yr, 27.6 kg, 17.3 kg/m(2)) completed the study. Mean error (mean percentage error) was 0.3 kg (1.6%), 0.2 kg (1.9%), and −1.3 kg (−4.1%) for 2D, 3D, and Broselow, respectively. Concordance between both TAPE devices and the Mercy Method was >0.99. The proportion of children predicted within 10% and 20% of actual weight was 76% and 98% for the 2D tape, and 65% and 93% for the 3D tape. Excluding the 209 (33%) children who were too tall for the device, Broselow predictions were within 10% and 20% of actual weight in 59% and 91%. CONCLUSIONS: The 2D- and 3D-Mercy TAPEs outperform the Broselow tape for pediatric weight estimation and can be used in a wider range of children.